2011
DOI: 10.1371/journal.pbio.1000585
|View full text |Cite
|
Sign up to set email alerts
|

Speeding Up Microevolution: The Effects of Increasing Temperature on Selection and Genetic Variance in a Wild Bird Population

Abstract: The authors show that environmental variation may lead to a positive association between the annual strength of selection and expression of genetic variance in a wild bird population, which can speed up microevolution and have important consequences for how fast natural populations adapt to environmental changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
214
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(228 citation statements)
references
References 47 publications
9
214
5
Order By: Relevance
“…See Table S1 for sample sizes Sequential model building involved testing with likelihood ratio tests (LRTs) (A) the effect of adding twoway interactions between year (coded as factor) and each of all traits and if found significant, then testing (B) the effect of each trait 9 year interaction independently of the other interactions Similar to our findings, the majority of these studies reported selection gradients that were negative for laying date, with earlier laying date being favourable, and positive for clutch size, with larger clutches being beneficial (e.g. different populations in Europe : Sheldon et al 2003;Garant et al 2007;Husby et al 2011b;Teplitsky et al 2011;Porlier et al 2012 Teplitsky et al 2014) being reported for these traits depending on the study system and species studied. Interestingly, the patterns of selection we documented here for morphological traitsselection favours heavier bird, does not affect wing length-are in contrast with the temporal phenotypic trends observed in our study system for females.…”
Section: Selection Patterns: Overall and Among Selection Episodessupporting
confidence: 76%
“…See Table S1 for sample sizes Sequential model building involved testing with likelihood ratio tests (LRTs) (A) the effect of adding twoway interactions between year (coded as factor) and each of all traits and if found significant, then testing (B) the effect of each trait 9 year interaction independently of the other interactions Similar to our findings, the majority of these studies reported selection gradients that were negative for laying date, with earlier laying date being favourable, and positive for clutch size, with larger clutches being beneficial (e.g. different populations in Europe : Sheldon et al 2003;Garant et al 2007;Husby et al 2011b;Teplitsky et al 2011;Porlier et al 2012 Teplitsky et al 2014) being reported for these traits depending on the study system and species studied. Interestingly, the patterns of selection we documented here for morphological traitsselection favours heavier bird, does not affect wing length-are in contrast with the temporal phenotypic trends observed in our study system for females.…”
Section: Selection Patterns: Overall and Among Selection Episodessupporting
confidence: 76%
“…One of these areas concerns the covariation between selection and genetic variation when both are affected by the same environmental factor 27, 84, 85 . A major assumption underlying the genetic accommodation mechanism is that there will be a positive relationship between the degree of genetic variation revealed and the strength of natural selection in novel environments.…”
Section: Ways Forward: Improving Our Understanding Of Plastic and Evomentioning
confidence: 99%
“…For example, in rich environmental conditions with ad libitum balanced food intake, among-individual variation in behavioural traits might be much higher than in a nutritionally impoverished environment (c.f. with imbalanced food availability) because the expression of genetic variation is typically increased under favourable conditions ([74, 75], but see [76]). This is because under nutritionally imbalanced conditions, most individuals fail to get enough resources (e.g.…”
Section: Multivariate Effects Of Nutritional Condition On Behaviouralmentioning
confidence: 99%